Моделирование фоновых температурных полей ДДВ - Лубков, М.В. (Геодинаміка, 2009)
Using facts of rifting origin and development of Dneprovsko-Donetsky hollow (DDH), it was carried out computer modeling of the phone temperature fields of the earth crust in the cross sections of Chernigov, Poltava and Harkov megablocks of DDH. It was showed, that visible distinctions of the temperature fields were fixed in the lower and middle parts of the crust, in the upper part, starting from 10 km layer, temperature fields were differed very little. Also the contribution of radioactivity, from 6 km layer consisted of approximately a third part of the near surface common phone temperature field. The temperature conditions in basalt layers of the lower crust demonstrated increasing of probability of the forming derivatives of eclogite metamorphism in the southeast direction. The comparison of the obtained results with the temperature measurements data in the upper crust part supports rifting origin theory of DDH.